2013
DOI: 10.1007/s12017-013-8242-1
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Prevents Synaptic Impairment Induced by Amyloid-β Oligomers Through α7-Nicotinic Acetylcholine Receptor Activation

Abstract: An emerging view on Alzheimer disease's (AD) pathogenesis considers amyloid-β (Aβ) oligomers as a key factor in synaptic impairment and rodent spatial memory decline. Alterations in the α7-nicotinic acetylcholine receptor (α7-nAChR) have been implicated in AD pathology. Herein, we report that nicotine, an unselective α7-nAChR agonist, protects from morphological and synaptic impairments induced by Aβ oligomers. Interestingly, nicotine prevents both early postsynaptic impairment and late presynaptic damage indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 97 publications
6
60
1
Order By: Relevance
“…Moreover, this protective effect of nicotine M a n u s c r i p t 47 was blocked by Į-BTX, consistent with its mediation by the Į 7 nAChR. Further, nicotine preserved pre-and postsynaptic contact that was disrupted by Aȕ oligomers, a protective effect that was blocked by Į-BTX [59]. Importantly, this Į 7 nAChR-mediated protective effect against the toxicity of Aȕ oligomers in cultured hippocampal neurons involved, at least in part, the PI3K/Akt signaling pathway because it could be blocked by wortmannin, an inhibitor of the PI3K/Akt signaling pathway.…”
Section: Procognitive and Neuroprotective Effects Of į 7 Nachr Agonistssupporting
confidence: 53%
See 2 more Smart Citations
“…Moreover, this protective effect of nicotine M a n u s c r i p t 47 was blocked by Į-BTX, consistent with its mediation by the Į 7 nAChR. Further, nicotine preserved pre-and postsynaptic contact that was disrupted by Aȕ oligomers, a protective effect that was blocked by Į-BTX [59]. Importantly, this Į 7 nAChR-mediated protective effect against the toxicity of Aȕ oligomers in cultured hippocampal neurons involved, at least in part, the PI3K/Akt signaling pathway because it could be blocked by wortmannin, an inhibitor of the PI3K/Akt signaling pathway.…”
Section: Procognitive and Neuroprotective Effects Of į 7 Nachr Agonistssupporting
confidence: 53%
“…Importantly, protective effects of nicotine (10 μM) against the toxic effects of a one hour incubation with oligomers of Aȕ 1-42 (5 μM) were shown in primary cultures of E18 rat hippocampal neurons [59]. Specifically, the Aȕ oligomers caused a significant reduction in the number of postsynaptic density protein-95 (PSD-95) clusters, a marker of the integrity of the postsynaptic architecture.…”
Section: Procognitive and Neuroprotective Effects Of į 7 Nachr Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was shown that intraventricular injection of Ab 1-42 inhibited the pressor response of the heart rate caused by choline infusion (Li and Buccafusco, 2004). Further agreement for an interaction between a7 nAChRs and Ab was obtained in studies relying on selective a7 nAChR agonists (Wang et al, 2010b;Chen et al, 2010;Inestrosa et al, 2013). A further complexity might reside in the structural differences between homomeric a7 and heteromeric a7b2 nAChRs, as shown by intracellular recording in brain slices and from nAChRs expressed in Xenopus oocytes .…”
Section: A Alzheimer's Diseasementioning
confidence: 93%
“…Evidence that soluble Aβ induces tau pathology has grown, with hyperphosphorylation as the primary pathological modification [18] . Extensive research has elucidated the role of the α7nAChR in the toxicity of soluble Aβ 42 and the consequent hyperphosphorylation of tau [19][20][21][22][23][24] . Soluble Aβ 42 in monomeric or oligomeric form binds and signals via α7nAChR [25][26][27][28] , essentially hijacking this receptor to abnormally activate various kinases [27,[29][30][31] to heighten tau phosphorylation.…”
Section: Aβ Signaling Via α7nachr To Hyperphosphorylate Taumentioning
confidence: 99%